ANALISA DAN PERANCANGAN SISTEM E-VOTING DALAM PEMILIHAN KETUA OSIS BERBASIS WEB PADA SMK MULTI MEDIA MANDIRI - Novi Yani; Redi Darmawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In entering the modern era and the rapid development of technology today, people are familiar with increasingly advanced and affordable technology to make it easier to carry out various activities in life. Technological progress is very rapidly occurring in various fields, for example in the fields of transportation, communication, health, education, and other fields so as to make people increasingly need technology to facilitate all the work in this life. The election of the Student Council Chairperson using this election system is a process of learning democracy directly for all students. In carrying out its activities the election of the student council president at a school is still often found using simple information delivery media in the form of only sheets of paper to convey a vision and mission, then even when the election is still using paper sheets to select candidates so that they are still not maximized. By utilizing computerized technology by using a web-based OSIS (e-voting) leader election application can make the selection of OSIS chair election activities easier in conveying information, faster in performing vote counts, and making more efficient on paper so that the results obtained can be effective and efficient . So it is necessary to conduct research to analyze, design and implement an E-Voting System for Student Council Chair with Web-based Election in Schools.